Moderating effect of situational strength on the relationship between personality traits and counterproductive work behaviour - Chuchai Smithikrai (2018)
The present study investigated the extent to which the strength of situations moderates the relations between personality traits and counterproductive work behaviour (CWB). It was hypothesized that the relations between personality traits and CWB would vary across strong and weak situations. In addition, there would be an interaction between conscientiousness and agreeableness in predicting CWB. As predicted, the results showed that the effect of personality on CWB depended on the strength of situations. The results also indicated that, in a weak situation only, conscientiousness has a stronger, negative relation to CWB when agreeableness is low than when agreeableness is high. © 2008 The Author.